Is 'Clinical' insight the same as 'Cognitive' insight in schizophrenia? - CORVIN, AIDEN PETER; GILL, MICHAEL; HAYDEN, JUDY (Cambridge University Press, 2009)
Poor insight is associated with impaired cognitive function in psychosis. Whether poor clinical insight overlaps with other aspects of self-awareness in schizophrenia, such as cognitive self-awareness, is unclear. We investigated whether awareness of clinical state (?clinical insight?) and awareness of cognitive deficits (?cognitive insight?) overlap in schizophrenia in a sample of 51 stabilized patients with chronic schizophrenia. Cognitive insight was assessed in terms of the agreement between subjective self-report and neuropsychological assessment. Patients who show good cognitive insight did not necessarily show good clinical insight. By contrast, self-report and objective neuropsychological assessment only correlated for patients in the intact clinical insight group and not for those in the impairment clinical insight group. We conclude that while good cognitive insight may not be necessary for good clinical insight, good cognitive awareness is at least partly reliant on the processes involved in clinical insight.
PUBLISHED
Keywords: Schizophrenia; Cognition; Insight; Cognitive failures; Sustained attention; Memory; Working memory